Comparison of Rice Yield among Farmer's Fertilizer Practices - Uchechukwu Paschal Chukwudi; Chinenye Ruth Arazu; Chidera Precious Okafor; Emmanuel Ikechukwu Eze; Nwando Geraldine Chukwudi; Olubukola Oluranti Babalola (Journal of Agricultural Extension)
The study examined rice farmers’ fertiliser purchasing behaviour and the impact of various fertiliser regimes on rice growth, yield, and grain nutrient content. Additionally, a field experiment using a randomised complete block design tested four treatments: no fertilizer (control), NPK20:10:10 (farmer’s practice), NPK20:10:10 + Single Superphosphate (SSP), and Urea + SSP. Results showed that while Urea + SSP improved growth metrics, NPK20:10:10+SSP achieved the highest grain yield (81 kg/plot) and 1000-seed weight (24.67 g), alongside elevated levels of iron and zinc, addressing both yield gaps and hidden hunger. These findings highlight the potential of phosphorus-enriched fertilizers to enhance productivity and nutritional outcomes in smallholder systems. The study underscores the importance of tailored, balanced fertilizer recommendations and sustainable interventions to address food security and malnutrition in Nigeria. Future research should explore these practices' scalability and long-term effects in diverse agrarian contexts.